Women’s Circle Approach is An Alternative Path for Gender Responsive Public Procurement System in Indonesia - Yusran, Sartiah; Mokodompit, Eliyanti Agus; Matoka, Ulfa (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2018)
Public procurement is a strategic public-sector function that has been recognized as a vehicle in supporting the government to achieve social goals and sustainable economic development. In line with this, gender inequality can be a significant constraint to economic growth and poverty reduction. Women procurement specialists have experienced inequality access and poor participation in the capacity building program and lack of contribution being leaders in public procurement managerial positions. Most females who attended the training have returned their certificates due to the challenges of being the procurement committee. These indicate female gaps, barriers, and obstacles in working as procurement specialists. The main purpose of this study is to identify the importance of Women’s Circle initiative to obtain additional support in increasing women’s capacity to provide services better and succeed in the profession; to improve skills and networking of women and access, participate and perform their tasks as the procurement professional. The study reveals that the issue of female procurement specialist is still ‘underground’ and programs related to female procurement profession remain ‘absent’. Gender stereotypes and discrimination indicate the main gaps to promote to the manager position, even though they have a high level of education, smart and also a good commitment to their work. Women are still recognized as the second group and are not allowed to play a leadership role, to some extent. This is due to the burden of domestic responsibilities that eventually catch up with them, making it difficult to remain in that role for an extended period of time. As a consequence, they have lack of self-confident, self-respect, self-esteem and also lack of capacities in communication and leadership skills and no motivation to promote themselves to the higher position. They agreed for the Women’s Circle initiative and this forum plays a vital role in supporting female professional capacity, enhancing the bargaining position and, empowering women to negotiate career development. Women’s Circle approach is a strategic path and potentially being an Educational and Training-based Forum or Learning-based forum; an agent of Reform-based Forum and as a Networking-based Forum. For a long-term benefit, Women’s Circle becomes an agent of change among women procurement specialist that finally led to being champions for Indonesian government procurement in reaching the quality of being more equitable, transparent and accountable. This approach is one of the indicators for increasing the quality of procurement modernization program with a gender perspective.